Penerapan Metode Bernyanyi dalam Meningkatkan Kosakata Bahasa Arab Siswa Kelas VII SMPIT Mutiara Makasar - Sulfitra, Sulfitra; R, Mantasiah; Latuconsina, Sarah Noviyanti; Fiddienika, Arif (Ta'limi | Journal of Arabic Education and Arabic Studies, 2023)
This study aims to determine the planning, process and results of increasing Arabic vocabulary using the singing method. This type of research is Classroom Action Research (CAR). The model used in this research is the Kemmis and Taggart class action research which consists of several stages, namely planning, implementation, action, data analysis at the reflection stage and the last stage is the result of data analysis. The subjects of this study were seventh grade students with a total of 27 students. Data collection techniques used are tests and observations. This study consisted of 2 cycles and each cycle consisted of 2 meetings. The results of this study indicate that in the first cycle the average value of learning outcomes obtained is 71% and in the second cycle the average value of learning outcomes obtained is 88.9%. Thus, there is an increase in learning outcomes from cycle 1 to cycle 2 of 17.9%. These results indicate that students' Arabic vocabulary mastery has increased by applying the singing method in learning Arabic